2010
DOI: 10.3340/jkns.2010.47.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Microsurgical Selective Tibial Neurotomy for Spastic Foot : Comparison of Adult and Child

Abstract: Objective : Selective neurotomy is generally a safe, effective, and long-lasting treatment for patients with spastic equinovarus foot deformity. We retrospectively analyzed the results of microsurgical selective tibial neurotomy (STN) for spastic feet in adults and children. Methods : A neurosurgeon selected 32 patients with 45 spastic feet (adults : 13, children : 32) to undergo microsurgical STN between October 1998 and September 2007. A physician of rehabilitation assessed spasticity pre-and postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…According to the studies about operative results of SPN, most focused on selective tibial neurotomy in the treatment of spastic equinus or equinovarus foot [24,25,26,27,28,29,30,31,32,33] while there have been a small number of reports with regard to surgical outcomes of hamstring and obturator neurotomy, including our study. Decq et al [34] used SPN in 11 patients who had excessive hamstring spasticity with a high Held’s score for restoration of bipodal stance and walking.…”
Section: Discussionmentioning
confidence: 92%
“…According to the studies about operative results of SPN, most focused on selective tibial neurotomy in the treatment of spastic equinus or equinovarus foot [24,25,26,27,28,29,30,31,32,33] while there have been a small number of reports with regard to surgical outcomes of hamstring and obturator neurotomy, including our study. Decq et al [34] used SPN in 11 patients who had excessive hamstring spasticity with a high Held’s score for restoration of bipodal stance and walking.…”
Section: Discussionmentioning
confidence: 92%
“…Although several studies have demonstrated the benefits of the STN for stroke patients, 7,8,14-16,30 some authors have also confirmed its effectiveness for other various etiologies of spastic foot (brain injury, spinal cord injury, multiple sclerosis, etc) 4,5,31-33 demonstrating that irrespective of the etiology of the spasticity, a large number of patients with equinovarus foot can improve their disability after both STN and rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…33 This situation could explain the deformity recurrence described by some authors. 29,32,[34][35][36] Also, the responsibility of a dystonic component (residual to neurotomy) may play a role in the recurrence of abnormal postures. In this way, Deltombe et al noted a gradual return of passive ankle dorsiflexion as long as 2 years after STN due to retraction of the Achilles tendon after a lack of stretching.…”
Section: Goal*mentioning
confidence: 99%